Pengaruh Fasilitas dan Kualitas Pelayanan terhadap Kepuasan Wisatawan pada Pemandian Air Panas Way Belerang Kecamatan Kalianda: Penelitian - Yudha Pratama Rusly; Tamam (Jurnal Pengabdian Masyarakat dan Riset Pendidikan, 2025)
The tourism sector in Indonesia is one of the service economic sectors that has bright prospects, but currently it has not shown a role that is in accordance with expectations in the development prospects in Indonesia. In the current era of globalization, tourism development is a top priority in supporting the development of a region. This study aims to determine the Effect of Facilities and Service Quality simultaneously on Tourist Satisfaction at the Belerang Hot Springs in Kalianda District. The sampling technique in this study used the Purposive Sampling method with a sample of 120 people. With the data collection technique using a questionnaire that has been tested for validity and reliability, the data analysis used is multiple regression analysis. The results of this study concluded that 1) Facilities have a positive effect on Tourist Satisfaction at the Kalianda District Hot Springs, Facilities with a regression coefficient in this study have a value of 0.196. 2) Service Quality has a positive effect on Tourist Satisfaction at the Kalianda District Hot Springs, Service Quality with a regression coefficient in this study has a value of 0.650. 3) Facilities and Service Quality Simultaneously have a positive effect on Tourist Satisfaction at Kalianda Hot Springs. This is proven by the results of the simultaneous f test in this study, which obtained a value of f count 43,352> f table 2.68 with a significance level of 0.000, which means that the hypothesis in this study, namely H3, is accepted and Ho is rejected.